Delta Urbanism coming of age: 25 years of Delta Urbanism where are we now? - Meyer, Han (Journal of Delta Urbanism, 2020)
‘Delta Urbanism’ is a common field of interest of different disciplines, which discovered the need to work together in order to be able to develop fruitful strategies for the future development of urbanized delta regions. The birth of this collaboration can be dated in the 1980s and 1990s, with the rise of three different fields of concern on the effects of industrial society: the concern on the environmental impact of industrialization, the concern on the alarming state of affairs of cities in these years, and the rising concern on climate change. The development of a real program of Delta Urbanism at TU Delft started in 2005, with the International Architecture Biennale Rotterdamon ‘the Flood’, the Katrina disaster in New Orleans and the start of the new Delta Program in the Netherlands as important driving forces. Important in the Delta Urbanism program is the search for a new ‘Darwinistic’ approach, emphasizing the evolutionary character of delta regions, and adaptivity as a main strategy to survive. This approach should substitute the traditional. Reductionist ‘Einstein’ approach, which is fitting in the dominating paradigm of the industrial society. Delta Urbanism itself can also be considered an evolutionary field of interest: it is under construction continuously. For the future, we can appoint four important issues to be elaborated: a more radical approach of the new adage ‘working with water’, water as a leverage for a complex society in transition; making delta landscapes adaptive, and design as an explorative method.